Consumer durables, monetary policy, and the green transition - Alexander M. Dietrich; Gernot J. Müller; Lukas Leitenbacher (Danmarks Nationalbank, 2025)
As part of the green transition, the European cap-and-trade scheme for CO2 emissions will be extended to cover consumer durables. We propose a New Keynesian model that features both, "brown" and "green" durable goods and show that if monetary policy follows a business-as-usual approach, the green transition will be inflationary, with headline inflation increasing by about 20 basis points over a fouryear transition period. Monetary policy faces a tradeoff: pursuing a strict inflation target will slow the green transition because green durable purchases are especially sensitive to interest rates. We quantify this tradeoff as we contrast headline and core-inflation targeting.
Keywords: E32; E52; E62; 330; Green transition; monetary policy tradeoff; consumer durables